Exploring the Effectiveness of the Adult Literacy Education Programme in Kano State, Nigeria - Isa, Aisha (Kulliyyah of Education, International Islamic University Malaysia, 2018)
This study explored the Effectiveness of Adult Literacy Education Programme (ALEP) in Kano State, Nigeria. It sought to understand the informants' perceptions of the ALEP implementation, the challenges and how they thought of overcoming those challenges. Guided by Knowle's (1984), adult learning theory, with adjunct of the Stufflebeam (2003), CIPP Model of evaluation, the research utilized qualitative method and followed a case study design confined to a selected adult literacy centre in the Municipal Local Government Area of Kano State, Nigeria. This was done to explore the perceptions of the adult learners, facilitators and the officials, who were directly involved in the implementation. By using purposive sampling technique, a total of 8 informants were selected to participate in the study. They were 4 adult learners, 2 facilitators and 2 officials. The instruments used to generate data were semi-structured interviews and non-participant observation. Two inter-raters were sought to identify the inter-rater reliability of the generated themes and sub-themes at 90.3% level of agreement. Also, member-check by experts and pilot study were done to ensure the credibility of the data. The findings of this study confirmed Knowle's theory of self-directedness of the adult learners who have unique needs that they wanted to be satisfied to make them participate in learning. All the participants agreed that the ALEP is a very important Programme and it was responsive to the economic and social needs of the adult learners. Nevertheless, there were weaknesses in implementing the Programme. Generally, both the officials and facilitators decried the Programme as being ineffective. In response to the challenges, all the informants complain on the challenges that they experience in the implementation of the ALEP, which was due to the unsuitable curriculum content, inadequate teaching equipment, lack of training of facilitators and poor funding, that according to officials and facilitators has led to the ALEP being unsatisfactory in terms of meeting the religious and cultural aspirations of the adult learners, leading to the facilitators adopting traditional teaching methods. Since they lack the competent training to teach using 21st century methods. Again, the adult learners, facilitators and officials agreed that the challenges in the ALEP, have contributed to high-rate of drop-outs and a decrease in the enrolment and the retention rates of adult learners. Also, since the current national curriculum of ALEP is not favourable, the policy makers should allow the design of a decentralised curriculum to cater for the varied needs of specific States, particularly for Kano State, that can allow the inclusion of religious components in the teaching materials and teaching methods that can motivate the adult learners to enrol and participate in the programme. Therefore, the findings provided an invaluable resource for designing two proposed all-inclusive curriculum models for facilitators and adult learners. These models are seen as a step forward in ensuring that, the facilitators are groomed in terms of personality of Murabbi (mentor), who will ensure that adult learners are guided with the right knowledge, skills and attitude of Insanul Kamil (holistic personality), to contribute towards the socio-cultural, cum-political, economic and religious development of the country.